Assessment of electrocardiography, echocardiography, and heart rate variability in dynamic and static type athletes - Ataei A (International Journal of General Medicine, 2012)
Mehrnoush Toufan,1 Babak Kazemi,1 Fariborz Akbarzadeh,1 Amin Ataei,1 Majid Khalili21Cardiovascular Research Center, Tabriz University of Medical Sciences, Tabriz, Iran; 2Azerbaijan National Academy of Sciences, Baku, AzerbaijanBackground: Over the last two decades, morphological cardiac changes induced by athletic conditioning have been of great interest. Therefore, several studies have been orchestrated to delineate electrocardiography (ECG), echocardiography, and heart rate variability (HRV) findings in athletes.Purpose: To assess the ECG, echocardiography, and HRV in a group of dynamic and static type athletes.Methods: Fifty professional athletes (20 static and 30 dynamic exercise athletes) and 50 healthy nonathletes (control group) were recruited. Standard 12-lead ECG and transthoracic echocardiography was performed on all athletes and the control group. Through echocardiography, variables including left ventricular (LV) end-diastolic/systolic diameter, LV mass, and left atrial volume index were measured. In addition, both the athletes and the control group underwent ECG Holter monitoring for 15 minutes and several parameters related to HRV (time and frequency domain) were recorded.Results: The most common ECG abnormalities among the athletes were sinus bradycardia and incomplete right bundle branch block. LV end-diastolic diameter and left atrial volume index were significantly greater in the dynamic athletes (P < 0.001). LV end-systolic diameter was significantly lower in the static group (P < 0.001). LV mass of the dynamic and static athletes was significantly greater than that of the controls (P < 0.001). Among the ECG Holter monitoring findings, the dynamic athletes had lower systolic blood pressure than the controls (P = 0.01). Heart rate was lowest in the control group (P < 0.001).Conclusion: The most common ECG abnormalities among adolescent Iranian athletes were sinus bradycardia and incomplete right bundle branch block. Static exercise seemed to reduce LV end-systolic diameter, while dynamic exercise resulted in increased LV end-diastolic diameter and left atrial volume index. Additionally, Iranian athletes showed no differences in HRV parameters, excluding heart rate and systolic blood pressure, compared with the nonathletes.Keywords: athlete's heart, electrocardiography, echocardiography, heart rate variability